Peran Budaya Organisasi dan Kualitas Sumber Daya Manusia Terhadap Kinerja Karyawan Pada Erlangga 2 Pusat Oleh-Oleh Khas Bali - Ni Komang Ayu Desi Purnama Sari; Ni Luh Ketut Ayu Sudha; Sucandrawati Sucandrawati; I Kadek Donny Wishanesta (Jurnal Visi Manajemen, 2024)
The phenomenon in this research is the lack of harmony in employee relations within an organization and the large number of employees who often arrive late which results in a lack of employees available to provide services to consumers which has an impact on not achieving targets. This research aims to determine the influence of organizational culture and the quality of human resources on employee performance. The location of this research was Erlangga 2, the Center for Typical Balinese Souvenirs. The research method used is quantitative and the data analysis techniques used are Multiple Linear Regression, Determination Coefficient, t Test and F Test. The sampling technique used in this research uses saturated samples. The population used in the research were all employees of the Erlangga 2 Balinese Souvenir Center and the sample used was 52 respondents. The results of the research can be seen that organizational culture has a positive and significant effect on employee performance, the quality of human resources has a significant positive effect on employee performance and organizational culture and the quality of human resources simultaneously have a significant effect on employee performance. The magnitude of the influence of organizational culture and human resource quality variables on employee performance is 52.5%.